2021
DOI: 10.1007/s00395-021-00868-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by post-conditioning with exogenous triiodothyronine in isolated perfused rat hearts and isolated adult rat cardiomyocytes

Abstract: Ischemic post-conditioning (iPoCo) by coronary re-occlusion/reperfusion during immediate reperfusion after prolonged myocardial ischemia reduces infarct size. Mechanical manipulation of culprit lesions, however, carries the risk of coronary microembolization which may obscure iPoCo’s cardioprotection. Pharmacological post-conditioning with exogenous triiodothyronine (T3) could serve as an alternative conditioning strategy. Similar to iPoCo, T3 may activate cardioprotective prosurvival pathways. We aimed to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 71 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…In contrast, the same dose of T3 in normal isolated perfused hearts did not have any effect on myocardial function. In accordance with this, a recent study has also shown that high-dose T3 administration at reperfusion can reduce infarct size and improve mitochondrial function [43]. Furthermore, high-dose T3 increased contractile recovery in human right atrial trabeculae subjected to hypoxia and reoxygenation [44].…”
Section: Differential Effects Of Th On Healthy and Injured Tissuesupporting
confidence: 54%
“…In contrast, the same dose of T3 in normal isolated perfused hearts did not have any effect on myocardial function. In accordance with this, a recent study has also shown that high-dose T3 administration at reperfusion can reduce infarct size and improve mitochondrial function [43]. Furthermore, high-dose T3 increased contractile recovery in human right atrial trabeculae subjected to hypoxia and reoxygenation [44].…”
Section: Differential Effects Of Th On Healthy and Injured Tissuesupporting
confidence: 54%
“…BS also improves responsiveness to endogenous thyroid hormones and decreases the levels of thyroid-stimulating hormone in obese patients 76 , 77 . These observations are important in the context of BS-mediated cardiac protection since it is known that thyroid hormones may increase myocardial tolerance to ischemia–reperfusion 78 , 79 .…”
Section: Discussionmentioning
confidence: 86%
“…Can exogenous FT3 supplementation improve prognosis in AMI patients? Previous animal studies had preliminary con rmed that administration of exogenous T3 after AMI had a myocardial protective effect [20], which similar to betablockers [21]. Pingitore et al further conducted a clinical trial involving 37 AMI patients with low T3 syndrome to observe the e cacy and safety of long-term oral synthetic T3.…”
Section: Discussionmentioning
confidence: 98%